Marketing digital y posicionamiento en el mercado de la corporación de productores y comercializadores orgánicos “BIO TAITA Chimborazo” – Coprobich 2017. - Mayra Lizbeth, Pilamunga Guallán (2020)
This degree project is a study to demonstrate that digital marketing affects an organization's market position, in this case the study focuses on the Organic Producers and Marketers Corporation "Bio Taita Chimborazo" - COPROBICH 2017, in order to relate digital marketing and market positioning towards a competitive approach and social impact of the corporation; prioritizing the satisfaction of its partners and consumers. The research is made up of five chapters which are divided: Chapter I: The referential framework is developed, which consists of approaching and formulating the problem, general and specific objective, justification. With this, knowledge about the needs of the company is obtained. Chapter II: It is made up of the theoretical framework, which is based on background, theoretical foundation and the analysis of each of the variables: digital marketing and market positioning corresponding to units 1 and 2. Chapter III: The methods used for the research, the type and design of the research, population and sample, techniques and instruments for information collection, information processing, data analysis and interpretation, and hypothesis calculation are described. Chapter IV: Once the three chapters have been analyzed, the conclusions and recommendations of the research are developed in relation to the initial problem. Chapter V: This chapter consists of the digital marketing proposal for the Organic Bio Taita Chimborazo Producers and Marketers Corporation - COPROBICH to achieve market positioning.